Factors Relating to the Presence of Escherichia Coli Bacteria in Beverages at the Area of Junior High School 1 Sukoharjo - Nurbaya, Fiqi; Ani, Nur; Sari, Dewi Puspito; Maharani, Nine Elissa; Indhun, Qomariah (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: There are many traders who sell beverages at the school at a cheap price, but delicious with a variety of flavors. A preliminary study at Junior High School 1 in Sukoharjo showed that 5 kinds of beverages sold at school contained Escherichia coli (E.coli) and some problems with food handlers occurred, such as not wearing head coverings and aprons. This study aimed to determine the association between food handler hygiene, equipment sanitation, water quality, and sanitation facilities with the presence of E. coli bacteria in beverages sold at the Junior High School 1 Sukoharjo area.Methods: This study used a cross-sectional design. The sampling method was total sampling. The sample size was 32 traders. Beverage samples of red and white syrup milk ice, macapuno coconut ice, milk tea ice, grass jelly ice, iced tea, milkshakes, hot tea, lemon tea ice, young coconut ice, sugar cane ice, Thai tea, chocolate ice, sour sugar ice. Data were collected through observation, interviews, and laboratory tests using total germ numbers. Chi-Square and Fisher Exact tests were used for the analysis.Results: There were associations between food handler hygiene, equipment sanitation, water quality, and sanitation facilities with the presence of E.coli bacteria in beverages in the Junior High School 1 Sukoharjo area, with the p values of 0.001, 0.001, 0.004, and 0.015 respectively.Conclusion: To reduce E. coli infection among the students, food handler hygiene, equipment sanitation, water quality, and sanitation facilities at the school should be improved., especially at Junior High School 1 Sukoharjo.